Silver Nanoparticles in the Water Environment in Malaysia : Inspection, characterization, removal, modeling, and future perspective - Achmad, Syafuddin; Salmiati, Salmiati; Hadibarata, Tony; Ahmad Kueh, Beng Hong; Mohd Razman, Bin Salim; Muhammad Abbas, Bin Ahmad Zaini (Springer Nature Publishing, 2018)
The current status of silver nanoparticles (AgNPs) in the water environment in Malaysia was examined and reported. For inspection, two rivers and two sewage treatment plants (STPs) were selected. Two activated carbons derived from oil palm (ACfOPS) and coconut (ACfCS) shells were proposed as the adsorbent to remove AgNPs. It was found that the concentrations of AgNPs in the rivers and STPs are in the ranges of 0.13 to 10.16mgL−1 and 0.13 to 20.02mgL−1, respectively, with the highest concentration measured in July. ACfOPS and ACfCS removed up to 99.6 and 99.9% of AgNPs, respectively, from the water. The interaction mechanism between AgNPs and the activated carbon surface employed in this work was mainly the electrostatic force interaction via binding Ag+ with O− presented in the activated carbon to form AgO. Fifteen kinetic models were compared statistically to describe the removal of AgNPs. It was found that the experimental adsorption data can be best described using the mixed 1,2-order model. Therefore, this model has the potential to be a candidate for a general model to describe AgNPs adsorption using numerous materials, its validation of which has been confrmed with other material data from previous works.